Inhibitory mechanism of catechins against advanced glycation end products of glycated myofibrillar protein through anti-aggregation and anti-oxidation. (July 2021) - Zhu, Zongshuai; Bassey, Anthony Pius; Khan, Iftikhar Ali; Huang, Ming; Zhang, Xibin
Abstract: Protein aggregation and oxidation could induce the generation of advanced glycation end products (AGEs). N ϵ -carboxymethyl lysine (CML), N ϵ -carboxyethyllysine (CEL) are two typical AGEs markers in muscle foods. Catechins are considered to be excellent natural antioxidants for scavenging AGEs in muscle protein. We compared, for the first time, the inhibitory effects and explored mechanisms of (−)-epigallocatechin (EGC), (−)-epigallocatechin-3-gallate (EGCG), (−)-epicatechin (EC), and (−)-epicatechin-3-gallate (ECG), in glycated myofibrillar protein (MPG) by measuring AGEs level, Maillard reaction degree, particle size and anti-oxidation ability using microstructure, multispectral and molecular docking techniques. The results showed that catechins dose-dependently inhibited AGEs in MPG through influencing lysine and free amino group, alleviating the Maillard reaction, detaching the particle size, affecting the protein-catechins interaction, relieving aggregates, and scavenging free radicals. The underlying mechanism behind the result indicated that catechins altered the structure information, SDS-PAGE bands, and the interaction sites of MPG via anti-aggregation and anti-oxidation. Particularly, EC and ECG showed weaker antioxidant ability than EGC and EGCG, EGCG exhibited a significant Pearson's correlation with the anti-oxidation and anti-aggregation of CML but no significant association with CEL. Overall, this study provides a theoretical insight into the applications of catechins to muscle foods as AGEs inhibitors. Highlights: Catechins inhibited the formation of advanced glycation end products (AGEs). The anti-AGEs mechanism was explored via multispectral and molecular docking. Catechin interacted with lysine and arginine to reduce AGEs. Catechin against the AGEs via anti-aggregation and anti-oxidation.